Corrosion Inhibition of Low Carbon Steel in Sulfuric Acid Using Polyvinyl Alcohol - Abdulwahab, Majid I.; Ahmed, Ayad B.; Yaro, Aprael S. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The inhibitive power of Polyvinyl Alcohol (PVA) was investigated toward the corrosion of carbon steel in 0.2N H2SO4 solution in the temperature range of 30-60˚C and PVA concentration range of 150-2000 ppm.   The corrosion rate was measured using both the weight loss and the electrochemical techniques. The weight loss results showed that PVA could serve as a corrosion inhibitor but its inhibition power was found to be low for the corrosion of carbon steel in the acidic media. Electrochemical analysis of the corrosion process of carbon steel in an electrochemical corrosion cell was investigated using 3-Electrode corrosion cell. Polarization technique was used for carbon steel corrosion in 0.2N H2SO4 solutions in presence and absence of the inhibitor investigated. Electrochemical runs were done in the PVA concentrations of 150, 1000, and 2000 ppm and temperatures of 30, 40, 50, and 60˚C.   It was shown that the inhibition efficiency for PVA decreased with increasing temperature at a given PVA concentration. On the other hand it was shown that at given temperature the inhibition efficiency of PVA was increased with increasing of PVA concentration in the corrosive acid until a PVA concentration of 2000 ppm was reached.   The Maximum inhibition efficiency reached was about 71 % at 30ºC and 2000 ppm concentration, calculated by the weight loss technique.  It was indicated also that the corrosion of carbon steel in 0.2N H2SO4 is highly activation controlled and inhibition action is occurring at both anodic and cathodic sites on the metal surface.